Analysis of Legal Capacity in Marriage Dispensation Applications Filed by Bridegroom Candidate - Rasikh Adila; Aprina Chintya (Rechtsnormen: Journal of Law, 2023)
Background. The filing of a case with the court must be done by a person who is legally competent and has legal standing for the case being filed. This legal capacity is related to the age of majority or maturity, as regulated in Article 330 BW. Purpose. This study aims to analyze the legal competence in an application for dispensation of marriage submitted by the bride-to-be herself as the applicant. This research uses a qualitative method with a descriptive analysis approach. Method. The type of research used is empirical normative legal research (applied legal research). This research uses secondary data with documentation data collection techniques. The document used in this research is the Decision of the Purwodadi Religious Court Number 198/Pdt.P/2018/PA.Pwd. The data analysis technique in this research is content analysis technique. Results. From this study, it was found that although in decision number 198/Pdt.P/2018/PA.Pwd the child can act as an applicant in a marriage dispensation case, Article 6 of Perma Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications has closed this opportunity so that when a child who is getting married is not old enough and does not have a parent or guardian, he cannot apply for marriage dispensation to the court. Conclusion. Based on the results of the above research, it can be concluded that civil legal capacity means a person's ability to perform legal acts and therefore be accountable for the legal consequences.